PERAN MODAL SOSIAL DALAM PENGELOLAAN HUTAN KEMASYARAKATAN KELOMPOK TANI REBAN LESTARI DESA BATU MEKAR KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - Qauliyah, Nurul; Setiawan, Budhy; Valentino, Niechi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
Social capital is considered a determinant of the success of community forest management. This research aims to determine the role of social capital in the sustainability of community forest management in the Reban Lestari farmer group. The respondents in this study were 67 members of the Reban Lestari forest farmer group. The level of social capital was analyzed using an equation between values ​​with 3 classes (low, medium and high) and to analyze the role of social capital in sustainable forest management, descriptive analysis was used. The research results show that social capital plays an important role in encouraging the development of community participation in sustainable forest management based on mutual trust, togetherness and proactive action.